PENGARUH PENDIDIKAN KESEHATAN DENGAN MENGGUNAKAN MEDIA AUDIOVISUAL DAN BOOKLET TERHADAP PENGETAHUAN, SIKAP DAN PERILAKU ORANGTUA DALAM MERAWAT BALITA DENGAN PNEUMONIA DI PUSKESMAS KECAMATAN CIPAYUNG DEPOK: PENGARUH PENDIDIKAN KESEHATAN DENGAN MENGGUNAKAN MEDIA AUDIOVISUAL DAN BOOKLET TERHADAP PENGETAHUAN, SIKAP DAN PERILAKU ORANGTUA DALAM MERAWAT BALITA DENGAN PNEUMONIA DI PUSKESMAS KECAMATAN CIPAYUNG DEPOK - Meylia, Meylia; Sulaeman, Suhendar; Heny Purwati, Nyimas (Ruang Ide Publisher, 2023)
Pneumonia is an acute infection and a picture of the lungs (alveoli), pneumonia in toddlers is characterized by symptoms of coughing so hard to breathe. The purpose of this study is health education with audiovisual media and books for parents with pneumonia toddlers, this research is a quasi-experiment, with non-equivalent without control group design pretest-posttest, there were 30 respondents in total, divided into 3 groups, 10 respondents were given health education using audiovisual media, 10 respondents used booklet media and 10 respondents were given audiovisual media and booklets. The tool used data for demographic data, questionnaire data to find out parents, and questionnaire to measure the attitude of parents. The results showed that there was a significant influence on knowledge, behavior, and behavior in caring for toddlers with pneumonia before and after it was done using audiovisual media, booklets at the level of knowledge p-value (0.0005), attitude value p-value (0.0005), and p-value behavior ( 0.0005), the use of Audiovisual intervals can be used when adequate health services, another alternative is the use of booklet media that can be used because it is easier and easier everywhere